P042 Decreased leukocyte trafficking may contribute to vedolizumab refractory disease after anti-TNF exposure in patients with ulcerative colitis. (16th January 2018) - Verstockt, B; Verstockt, S; de Bruyn, M; Machiels, K; Blevi, H; Ballet, V; Van Assche, G; Vermeire, S; Ferrante, M
Abstract: Background: Vedolizumab (VDZ) limits lymphocyte recruitment to the gut by targeting the α4β7 integrin and has shown efficacy in patients with ulcerative colitis (UC). Real-life and controlled trial data suggest that VDZ is more effective in anti-TNF naïve patients. We studied proteomic and transcriptomic differences between patients with and without anti-TNF exposure prior to VDZ initiation. Methods: Serum samples of 63 UC patients (50.8% female, median disease duration 8.3 years) with baseline endoscopic active disease were prospectively collected prior to VDZ treatment, as well as serum from 69 healthy controls. Using Proximity Extension Assay technology (Olink Inflammation), proteomic analysis was performed on baseline serum samples. Biopsies from inflamed colon in 16 UC patients were taken prior to VDZ initiation. Mucosal total RNA was isolated, and next-generation sequencing performed using Illumina HiSeq 4000NGS. Differential gene expression was evaluated by DESeq R package and pathway analysis by Ingenuity Pathway Analysis. Results: Prior to VDZ therapy, 80.6% of patients received ≥1 anti-TNF agents. By comparing anti-TNF experienced and naive patients before first VDZ administration, five proteins were significantly overexpressed in the naïve population ( p < 0.05), including CCL25 (fold change (FC) 1.43) (Figure 1). This association was mainly driven by previous infliximab (IFX) exposure ( p = 0.031). Pathway analysis revealed a significant upregulation of regulatory pathways involved in leukocyte chemotaxis, cell migration and leukocyte migration in the naïve population ( p < 0.005). CCL25 levels in all UC patients were similar compared with healthy controls ( p = 0.35, FC 1.0), thus not reflecting disease activity. No significant correlation between CCL25 and disease duration or duration of anti-TNF therapy could be observed. In patients exposed only to IFX prior to VDZ, CCL25 was significantly lower when IFX was stopped less than one year prior to VDZ initiation ( p = 0.021). Inflamed colonic biopsies from anti-TNF naïve patients expressed numerically more CCL25, compared with anti-TNF experienced patients (FC 25.0). Serum prior to both anti-TNF and subsequent VDZ therapy was available in 11 patients. Paired-analysis showed that patients who responded to VDZ ( n = 6) had overall a stable CCL25 from start of anti-TNF to start of VDZ ( p = 0.88), whereas patients who failed VDZ therapy ( n = 5) experienced a drop in CCL25 ( p = 0.12). Conclusions: Prior administration of IFX significantly influences leukocyte trafficking and may therefore mechanistically explain lower VDZ response rates after prior anti-TNF therapy in UC. Although further experimental evidence is warranted, we hypothesise that IFX downregulate CCL25, which has shown to influence α4 β7-MADCAM1 adhesion.